2020
DOI: 10.3390/math8091423
|View full text |Cite
|
Sign up to set email alerts
|

Fast COVID-19 and Pneumonia Classification Using Chest X-ray Images

Abstract: As of the end of 2019, the world suffered from a disease caused by the SARS-CoV-2 virus, which has become the pandemic COVID-19. This aggressive disease deteriorates the human respiratory system. Patients with COVID-19 can develop symptoms that belong to the common flu, pneumonia, and other respiratory diseases in the first four to ten days after they have been infected. As a result, it can cause misdiagnosis between patients with COVID-19 and typical pneumonia. Some deep-learning techniques can help physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Nowadays, a huge number of CNN models exist and are used for distinct purposes. As a result, we can find custom models [ 16 , 19 , 31 ] and the ones that use key baselines for classification of different diseases [ 17 , 22 , 24 , 29 , 41 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, a huge number of CNN models exist and are used for distinct purposes. As a result, we can find custom models [ 16 , 19 , 31 ] and the ones that use key baselines for classification of different diseases [ 17 , 22 , 24 , 29 , 41 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Yu et al [ 23 ] presented a framework that used four pretrained CNNs as baseline to classify among patients using CT scans, obtaining accuracies superior to 94%. Luján-García et al [ 24 ] used an Xception CNN to classify among COVID-19 and pneumonia patients using a pretrained model on ImageNet. They showed that the Xception network was the fastest among several baselines.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the number of parameters is substantially reduced, feature propagation is strengthened. The same residual block is defined in [1] through the linear operators K 1 and K 2 , while the parameter vector Θ has three parts: Θ (1) and Θ (3) for weights W 1 and W 2 from Equation (1), respectively Θ (2) for parameters of the normalization layer N . The residual block output is defined by Equation (2), where σ is the activation function, and Y is the input vector.…”
Section: Theoretical Aspects For Pde Inspired Neural Networkmentioning
confidence: 99%
“…The residual block output is defined by Equation (2), where σ is the activation function, and Y is the input vector. The transformation of a network with several layers with ResNet blocks, input Y 0 and N layers is described in (3). F(Θ, Y) = K 2 (Θ (3) )σ(N (K 1 (Θ (1) )Y, Θ (2) ))…”
Section: Theoretical Aspects For Pde Inspired Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation